Analysis of an Air Source Heat Pump Space Cooling System under Variable Inlet Water Temperature Condition - Jin Chengcheng; Wang Ruzhu; Zhai Xiaoqiang; Jin Zhequan (Zhileng xuebao)
In order to enhance the operating performance of air source heat pump, the performance of air source heat pump (ASHP) system with the variable inlet water temperature strategy was experimentally studied. As field test shows, the condition of variable outlet water temperature could satisfy the indoor cooling demmand. Compared with traditional ASHP cooling system adopting fixed 12 ℃ inlet water temperature, this kind of system is proved to be with higher COP and lower power consumption, and therefore is an obvious energy saving system. In addition, the Dymola model was established to verify the experimental results, and the simulation of energy consumption of actual air conditioning system was conducted based on the model. The results indicated that COP would improve 10 percent from 3.99 to 4.39.